Removals of ammoniacal nitrogen, orthophosphate, biochemical oxygen demand, chemical oxygen demand and total suspended solids in subsurface flow constructed wetland: A short review - Chong, Harry Lye Hin; Lim, Jian Min; Rubia Idris; Thau, Wilson Lym Yong (UniSE Press, 2024)
Subsurface flow constructed wetland has been known for its capability to treat wastewater. This work reviewed the removals of ammoniacal nitrogen, orthophosphate, biochemical oxygen demand, chemical oxygen demand and total suspended solids recently published in Scopus indexed journals. Ammoniacal nitrogen in subsurface flow constructed wetland was removed via six interconnected mechanisms, namely, nitrification-denitrification, partial nitrification denitrification, anaerobic ammonium oxidation, plant uptake, volatilisation and adsorption. The orthophosphate was removed via chemical and biological mechanisms such as adsorption, ligand exchange, precipitation, plant uptake and biological storage in microorganisms. Organic matter in the constructed wetland basin was treated via aerobic and anaerobic degradations to reduce the biochemical oxygen demand and chemical oxygen demand, respectively. Physical mechanisms such as filtration, adsorption and gravitational settling were responsible for the removal of total suspended solids. There exist data gaps which were the application of emergent non-aquatic angiosperms as constructed wetland plants and the simultaneous treatment of ammoniacal nitrogen, orthophosphate, biochemical oxygen demand, chemical oxygen demand and total suspended solids in a single integrated experiment has not been experimented. Future subsurface flow constructed wetland research can address these data gaps.